Potential for Developing Cloudfisher Technology (Fog Catcher) as a Source of Consumption Water in Fakfak Regency: Potensi Pengembangan Teknologi Cloudfisher (Penangkap Kabut) Sebagai Sumber Air Konsumsi Di Kabupaten Fakfak - Muhlisah, Nurul; Jusmawandi; Niswati Tarman, Risma (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The geomorphological condition of Fakfak Regency is dominated by limestone. It makes ground water difficult to access. The clean water crisis in Fakfak Regency requires people to look for alternative sources of clean water such as rainwater. However, during the dry season, people will have great difficulty with clean water. Cloudfisher or fog catcher is a technique for collecting fog that have condensed into water. Cloudfisher's ability to catch fog or dew and produce water varies depending on the situation with an average of around 2 liters – 10 liters/m2/day. The ability of this technology to produce water depends on the net material used, the size of the net, the direction and model of the net, and the location of the net placement. In this research, the potential cloudfisher to produce water in Fakfak Regency will be examined, with the ultimate aim of seeing how effectively this technology is applied in Fakfak Regency in terms of the amount of water produced. The method used in this research is a field study by reviewing locations in Fakfak Regency with the altitude, fog conditions, temperature and humidity that are most suitable for the application of cloudfisher technology. The fog catcher was installed using a standard research model using 65% and 85% cover nets. Each fog catcher material was installed for 1 month and the amount of water captured by the tool was checked every morning at 06.30 am. The location of the fog catcher is based on several factors including altitude, air humidity, fog frequency, temperature and wind speed. The average water volume obtained in the 65% cover net was 59.6 ml while in the 85% cover net it was 26.24 ml. Factors that influence the amount of water obtained are net material, net cover, fishing area, equipment placement, and weather. The fog catcher (cloudfisher) in Fakfak Regency has the potential to be used but still requires further research regarding the design and materials used so that more water can be obtained and can be used by local communities as an alternative source of clean water